The Ketogenic Diet and Its Effect on Bone Mineral Density: A Retrospective Observational Cohort Study - Draaisma, Jos M.T.; Hampsink, Brieke M.; Janssen, Marcel; van Houdt, Nicole B.M.; Linders, E. T.A.M.; Willemsen, Michèl A. (Neuropediatrics, 2019)
Background During long-term follow-up of children treated with the ketogenic diet therapy (KDT) have an increased incidence of bone fractures. However, the exact contribution of KDT to a decreased bone mineral density (BMD) remains unclear.Objective This study aimed to evaluate (changes in) BMD in children treated with KDT and to evaluate whether intravenous bisphosphonate therapy may be effective.Design In this retrospective, observational cohort study, all children treated with KDT from 2010 until 2018 at the Radboudumc Amalia Children's hospital were included. Patients who were on KDT for more than 6 months and who had at least two dual-energy X-ray (DXA)-scans were eligible for inclusion for longitudinal analysis. Z-scores of DXA-scans were compared over the course of time.Results In 34 out of 68 patients, one or more lumbar DXA-scans were performed, with a mean lumbar Z-score of −1.32 ± 1.74. Of these 68 patients, 8.8% got a fracture during KDT, and also 8.8% got kidney stones. In 20 patients, more than one DXA-scan was performed. A statistically not significant decrease in BMD (0.22 Z-score/year) was found. However, there was an increase in BMD in the five patients treated with intravenous bisphosphonate therapy. This was statistically significant in comparison to the nonbisphosphonate treated group (p = 0.034).Conclusion Children on KDT have low normal BMD which may decrease further during KDT. For this reason monitoring of BMD is crucial, as is monitoring of kidney stones and hypercalciuria. Intravenous bisphosphonate therapy may have a positive effect, when other therapies have failed.
Keywords: ketogenic diet tehrapy; bone mineral density; biphophonate therapy; epilepsy